Etiological and Clinical Profile of Acute Hepatitis in Children: Experience of A Tertiary Care Hospital in Bangladesh - Haque, Emdadul; Hasan, Ahmed Rashidul; Farhana, Tanzila; Mahmud, Salahuddin (Dhaka Shishu (Children) Hospital Journal, 2026)
Background: Acute hepatitis is a major public health concern, affecting millions of children worldwide . The four most frequent viruses that cause infection are hepatitis A, B, C, and E. The etiology of acute viral hepatitis varies depending upon several epidemiological and individual factors. Objective: The study aimed to determine the etiology and clinical characteristics of acute hepatitis in pediatric patients in a tertiary care hospital. Methods: This cross-sectional study was conducted in the Department of Pediatric Gastroenterology, Hepatology, and Nutrition, Bangladesh Shishu Hospital & Institute (BSH&I) from January 2023 to January 2024. A total of 50 children aged 1 to 12 years, presenting with acute hepatitis of various etiologies, were included. Acute hepatitis was diagnosed based on clinical manifestation (jaundice lasting <3 months without any stigmata of chronic liver disease) and biochemical evidence of elevated alanine aminotransferase (ALT) and aspartate transaminase (AST). Specific serological markers were used to determine the etiology of acute hepatitis. Data were analyzed by using SPSS version 25 Results: Acute hepatitis was common in children aged 6- to 10-year-old age group (52%), with a mean age of 8.9±3.3 years. The majority of affected children were male (62%), while females accounted for 38%. Common clinical features were jaundice (92%), nausea and vomiting (88%), abdominal pain (70%), hepatomegaly (80%), fever (64%), dark urine (62%), yellow eyes (58%), and decreased appetite (24%). The Etiological profile showed:Hepatitis A virus is 35 (70%) had hepatitis A virus, 5 (10%) had hepatitis E virus, 2 (4%) had hepatitis B virus, 3 (6%) had Salmonella hepatitis, 2 (4%) had Wilson’s disease, and 1 (2%) had hepatitis C virus, hepatitis A+E virus, anti-TB, and valproic acid each. Conclusion: The most prevalent etio-logical agent was hepatitis A, followed by hepatitis B and hepatitis E. Additionally, a mixed hepatitis A and E infection was observed . Common clinical features were jaundice, nausea & vomiting, abdominal pain, hepatomegaly, fever, dark-colored urine, yellow eyes, and decreased appetite. DS (Child) H J 2024; 40(1): 30-34